THE IMPLEMENTATION OF SOCIO-ECONOMIC AND GOOD GOVERNANCE MODELS IN IMPROVING ZAKAT COMPLIANCE BEHAVIOR AMONG ENTREPRENEURS IN ACEH PROVINCE, INDONESIA - Riyaldi, Muhammad Haris; Syahriyal; Munzil (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
The Aceh government issued an appeal letter No.180/11860 dated August 3 2022 regarding an appeal to Muslim employees and companies (businesses) to deposit their zakat to Baitul Mal. The compliance behavior of entrepreneurs paying zakat to Baitul Mal is an important concern in optimizing zakat receipts in Aceh. Socio-economic models and good governance are important factors in increasing zakat compliance among entrepreneurs. What are Baitul Mal Aceh's policies and strategies for optimizing these two models? This research was conducted using a qualitative descriptive approach. Data was collected using interview and documentation techniques. Data analysis uses data reduction techniques, data display and conclusion making. The research results show that Baitul Mal Aceh has strengthened zakat management regulations in Aceh and followed this with education and socialization. Apart from that, Baitul Mal also always displays information related to the collection and utilization of zakat funds. Management with good governance is carried out by prioritizing transparency and accountability in zakat management. It is hoped that optimizing zakat continues to prioritize socio-economic models and good governance and can increase the trust and interest of entrepreneurs so that in the end they give their zakat to Baitul Mal Aceh.